Proteomic and physiological approaches reveal new insights for uncover the role of rice thylakoidal APX in response to drought stress - Cunha, Juliana R.; Carvalho, Fabrício E.L.; Lima-Neto, Milton C. [UNESP]; Jardim-Messeder, Douglas; Cerqueira, João Victor A.; Martins, Marcio O.; Fontenele, Adilton V.; Márgis-Pinheiro, Márcia; Komatsu, Setsuko; Silveira, Joaquim A.G. (Elsevier, 2018)
Chloroplast APX isoforms display controversial roles as H2O2 scavengers and signaling players in response to abiotic stress and conclusive results are lacking. We tested the hypothesis that thylakoidal APX displays an important role for drought tolerance, especially by regulating abundance of essential protein species. For this, OsApx8 RNAi-silenced rice (apx8) and non-transformed plants (NT) were exposed to mild water deficit. The drought-sensitivity in apx8 plants was revealed by decreases in shoot growth, relative water content and photosynthesis, which was accompanied by increased membrane damage, all compared to NT plants. This higher sensitivity of apx8 plants to mild drought stress was also related to a lower accumulation of important protein species involved in several metabolic processes, especially photosynthesis, photorespiration and redox metabolism. Despite apx8 plants have displayed an effective induction of compensatory antioxidant mechanisms in well-watered conditions, it was not enough to maintain H2O2 homeostasis and avoid oxidative and physiological disturbances under mild drought conditions. Thus, thylakoidal APX is involved in several phenotypic modifications at proteomic profile level, possibly via a H2O2-induced signaling mechanism. Consequently, this APX isoform is crucial for rice plants effectively cope with a mild drought condition. Biological significance: This work provides for the first time an integrative study involving proteomic, physiological and biochemical analyses directed to elucidation of thylakoidal APX roles for drought tolerance in rice plants. Our data reveal that this enzyme is crucial for maintaining of growth and photosynthesis under mild water deficit conditions. This essential role is related to maintaining of H2O2 homeostasis and accumulation of essential proteins involved in several important metabolic pathways. Remarkably, for drought resistance was essential the accumulation of proteins involved with metabolism of photosynthesis, signaling, carbohydrates, protein synthesis/degradation and stress. These results can contribute to understand the role of chloroplast ascorbate peroxidases in drought tolerance, highlighting the physiological importance of key proteins in this process.
Keywords: Ascorbate peroxidases; Oryza sativa; Photosynthesis; Proteome; Redox metabolism; Water deficit